L'Italiana in Algeri = The Italian girl in Algiers - Fisher, Burton D. (Opera Journeys mini guide series., 2000)
A comprehensive guide to Rossini's L'ITALIANA IN ALGERI, featuring Principal Characters in the opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and an insightful and in depth Commentary and Analysis by Burton D. Fisher, noted opera author and lecturer.